Fruit Pomaces as Functional Ingredients in Poultry Nutrition: A Review - Mnisi, Caven Mguvane; Mhlongo, Godfrey; Manyeula, Freddy (Frontiers in Animal Science, 2022)
Sustainable poultry intensification is economically constrained by several factors including high feed costs, which constitute more than 70% of total production costs. Functional feed ingredients such as fruit pomaces can be incorporated into poultry diets as natural sources of nutrients and biologically active substances to deliver sustainable production. Fruit pomaces are agro-industrial waste by-products that have no direct food value for humans. Their utilisation as feed ingredients would reduce feed-food competitions, optimize poultry production systems, and promote environmental, economic, and social sustainability. Large quantities of fruit pomace wastes are generated and disposed in landfills or through incineration with little regard to the environment. Thus, their inclusion in poultry feeds could offer a long-term strategy to protect the environment. Valorising fruit pomaces to enhance poultry production would also contribute towards sustainable development goals and food security through the provision of affordable high-quality protein to the rapidly growing human population. Moreover, the use of fruit pomaces complements food production systems by ensuring that food animals are reared on human inedible feedstuffs. Thus, this review explores the nutritional composition and subsequent feeding values of various fruit pomaces, while examining their environmental benefits when used as feed ingredients in poultry nutrition. Furthermore, strategies that can be employed to negate the effect of anti-nutritional factors in the pomaces are presented. We postulate that the use of fresh or valorised fruit pomaces would improve poultry production and significantly reduce the amounts of waste destined for incineration and/or direct deposition in landfills.